Early life factors and risk of childhood rhabdomyosarcoma - Anshu eShrestha; Anshu eShrestha; Beate eRitz; Simona eOgnjanovic; Christina A Lombardi; Michelle eWilhelm; Julia eHeck (Frontiers Media S.A., 2013)
Although little is known about etiology of childhood rhabdomyosarcoma, early life factors are suspected in the etiology. We explored this hypothesis using linked data from the California Cancer Registry and the California birth rolls. Incident cases were 359 children < 6 year old (218 embryonal, 81 alveolar, 60 others) diagnosed in 1988-2008. Controls (205,173), frequency matched on birth year (1986-2007), were randomly selected from the birth rolls. We examined association of birth characteristics such as birth weight, size for gestational age, and timing of prenatal care with all-type rhabdomyosarcoma, embryonal and alveolar subtypes. Crude and adjusted odds ratios (ORs) and 95% confidence intervals (95% CIs) were estimated using logistic regression. In contrast to a previous study, we observed statistically non-significant association for embryonal subtype among high birth weight (4000-5250 grams) children for term births [OR (95%CI): 1.28 (0.85, 1.92)] and all births adjusted for gestational age [OR (95%CI): 1.21 (0.81, 1.81)]. On the other hand, statistically significant 1.7-fold increased risk of alveolar subtype (95%CI: 1.02, 2.87) was observed among children with late or no prenatal care and a 1.3-fold increased risk of all rhabdomyosarcoma subtypes among children of fathers ≥ 35 years old at child birth (95%CI: 1.00, 1.75), independent of all covariates. Our finding positive association on male sex for all rhabdomyosarcoma types is consistent with previous studies. While we did not find a convincingly positive association between high birth weight and RMS, our findings on paternal age at childbirth and prenatal care supports the hypothesis that prenatal environment modifies risk for childhood rhabdomyosarcoma.